Some Remedies from Ḥubaiš AL-Aʿsam* - Kahl, Oliver (Journal of Semitic studies, 2008)
This article deals with eight remedies from an otherwise lost pharmacological work of the Christian Arab translator-physician Ḥubaiš al-Aʿsam ad-Dimašqī (fl. second half of third/ninth century). The remedies, preserved as quotations in ar-Rāzīʾs (d. 313/925 or 323/935) medical encyclopedia al-Ḥāwī, are re-edited here, translated into English, and supplemented by an index of botanical names.